Frailty index to predict all-cause mortality in Thai community-dwelling older population: A result from a National Health Examination Survey cohort - V. Srinonprasert (2019)
© 2018 Background: Frailty is a clinical state of increased vulnerability from aging-associated decline. We aimed to determine if a Thai Frailty Index predicted all-cause mortality in community-dwelling older Thais when accounting for age, gender and socioeconomic status. Methods: Data of 8195 subjects aged 60 years and over from the Fourth Thai National Health Examination Survey were used to create the Thai Frailty Index by calculating the ratio of accumulated deficits using a cut-off point of 0.25 to define frailty. The associations were explored using Cox proportional hazard models. Results: The mean age of participants was 69.2 years (SD 6.8). The prevalence of frailty was 22.1%. The Thai Frailty Index significantly predicted mortality (hazard ratio = 2.34, 95% CI 2.10–2.61, p < 0.001). The association between frailty and mortality was stronger in males (hazard ratio = 2.71, 95% CI 2.33–3.16). Higher wealth status had a protective effect among non-frail older adults but not among frail ones. Conclusions: In community-dwelling older Thai adults, the Thai Frailty Index demonstrated a high prevalence of frailty and predicted mortality. Frail older Thai adults did not earn the protective effect of reducing mortality with higher socioeconomic status. Maintaining health rather than accumulating wealth may be better for a longer healthier life for older people in middle income countries.